Implementasi Pembelajaran Al-Qur'an Braille dalam Pendidikan Agama Islam bagi Yatim Piatu Tunanetra - Syamsul Muqorrobin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research aims to analyze the Implementation of Braille Al-Qur'an Learning in Islamic Religious Education for Blind Orphans. Data retrieval techniques with documentation from journal data on Google Scholar. Data analysis technique using Systematic Literature Review. The implementation of learning the Braille Al-Qur'an in Islamic religious education for blind orphans has a significant positive impact. Through the use of the Braille method, blind students can access the text of the Koran more independently and effectively, enabling them to understand and memorize the holy verses. In addition, this approach opens the door to equal access to Islamic religious education for those with visual impairments. With this implementation, blind orphans can feel the presence of the Koran in their daily lives, enrich their spirituality, and help them develop the values ​​of faith. Thus, implementing Braille Al-Qur'an learning in the Islamic religious education environment is a progressive step in ensuring inclusivity and accessibility for all orphans, especially for those with special needs.